The Role of Socioeconomic Position in Determining Tooth Loss in Elderly Costa Rican: Findings from the CRELES Cohort - Barboza Solís DDS, MSc, PhD, Cristina (2017)
Objective: Differences in health status between socioeconomic groups continue to challenge epidemiological research. To evaluate health inequalities in tooth loss, using indicators of socioeconomic position (education level, occupation and subjective economic situation), in a large representative sample of elderly Costa Ricans, can contribute to conceive better adapted public health interventions. Methods: Data are from the Costa Rican Longevity and Healthy Aging Study (CRELES Pre-1945), a longitudinal study of a nationally representative sample of elders. 2827 participants were included in the study using data from the first wave conducted in 2005, and analyzed cross-sectionally. The sample was imputed for missing data using a multiple imputation model. Tooth loss was self-reported and informed about the quantity of missing teeth. Information on participant’s socioeconomic factors was collected via a questionnaire, including three measures approaching socioeconomic position: education level, occupation and subjective economic situation. Additional variables were included in the multivariate analyses as potential confounders. Results: Tooth loss was found to be strongly socially patterned, using variables characterizing socioeconomic position, mainly education level, occupational status and subjective economic situation. Conclusions: To highlight how socioeconomic position relates to tooth loss, can allow a better understanding of the origins of the social gradient in oral health, to tackle the most common chronic diseases across the world.